Enhancement of Magnetic and Microwave Absorbing Properties of [Ba (Fe, Mn, Ti)12 O19]1-x–[CoFe12 O4] x (x = 0.2; 0.5; 0.8) Composites. (March 2020) - Darmawan, L.; Suparno; Manaf, A.
Abstract: In this paper, we report magnetic and microwave absorbing properties of magnetic based nanocomposite, which synthesized through mechanically alloyed the magnetic crystalline powders. The first component of composite was Mn-Ti doped Barium hexaferrite(BaFe12O19) or BHF obtained through a mechanical alloying process which was mixed with the second component of mechanically alloyed the CoFe2O4magnetic compound to form composites of [Ba (Fe, Mn, Ti)12 O19 ]1-x –[CoFe2 O4 ]x (x = 0.2; 0.5; 0.8) compositions. Prior to composite the two magnetic components, the remanence and saturation magnetization of the components were obtained optimally. Before Mn-Ti doping, the BHF has remanence (Mr) and saturation magnetization 0.206 T and 0.42 T respectively, with the corresponding coersivity (Hc) was 263.1 kA/m. On the other hand, CoFe2O4 (CFO) which has a high saturation magnetization(0.48 T) but with a low coersivity(16.22 kA/m). In form of magnetic composite, the high remanence was almost retained, but with the coersivity value decreased further to the lowest 80.82 kA/m. These two main properties (high remanance and low coersivity) were led the composite being good candidates for microwave absorbing materials. Microwave absorbing characteristics of [Ba(Fe, Mn, Ti)12 O19 ]1-x –[CoFe2 O4 ]x (x = 0.2; 0.5; 0.8) composites were discussed in this paper relation with their corresponding magnetic properties for designing the best microwave absorbing materials.